SYNERGIZING GREEN HOSPITAL MANAGEMENT AND CARBON ACCOUNTING: A FRAMEWORK FOR SUSTAINABLE HEALTHCARE INNOVATION - Muhammad Alfatih; Dimas Dwi Gustanto; Ade Sudarma; Andri Indrawan (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This study develops a conceptual framework that integrates green hospital management and carbon accounting to support sustainable healthcare innovation. Method: This study uses a literature review and conceptual paper approach by synthesizing recent studies, sustainability frameworks, healthcare management practices, and carbon accounting principles. Results: The findings propose an integrated framework consisting of five strategic pillars: sustainable governance, green operational systems, carbon measurement and disclosure, circular healthcare resource management, and digital sustainability innovation. The framework demonstrates that carbon accounting can function not only as a reporting tool but also as a strategic instrument for efficiency, cost control, regulatory compliance, and long-term hospital resilience. Novelty: This study contributes theoretically by bridging sustainability accounting and healthcare management literature and practically by offering a roadmap for hospital administrators and policymakers. The proposed model supports environmentally responsible healthcare systems while maintaining service quality and operational effectiveness.